Assessing delayed penicillin hypersensitivity using the PENFAST+ score - Castagna, Julie; Chasset, François; Autegarden, Jean-Eric; Le Thai, Claire; Amsler, Emmanuelle; Barbaud, Annick; Soria, Angèle (Frontiers in Allergy, 2023)
Introduction Approximately 10% of individuals report a suspected allergy to penicillin, but according to allergy work-ups, only 10% to 15% of them are truly allergic. A clinical decision score, the PEN-FAST, was developed and validated to identify adults with low-risk penicillin allergy. Objectives The objective of this study was to improve the performance of the PEN-FAST score, particularly for those with delayed hypersensitivity (HS), by improving the negative predictive value. Methods STEP 1: Retrospective evaluation of the PEN-FAST score in patients with proven immediate and delayed penicillin allergy. STEP 2: Identification of additional criteria among Step 1 patients misclassified by PEN-FAST score. Development of the PEN-FAST+ score using multivariable logistic regression in a prospective cohort of patients with a suspicion of HS to penicillin. STEP 3: Comparison of diagnostic performances of PEN-FAST and PEN-FAST+ scores. Results The PEN-FAST score showed limitations in predicting the relapse of immediate skin HS or delayed maculopapular exanthema, with 28.6 and 38.4% of patients misclassified, respectively. We identified two potential additional criteria: skin rash lasting more than 7 days and immediate reaction occurring in less than 1 hour (generalized or localized on palmoplantar area or scalp itching/heat feeling). A total of 32/252 (12.7%) patients were confirmed to be allergic to penicillin. With PEN-FAST, 37% of patients (n=10) with delayed allergic penicillin HS were misclassified. With PEN-FAST+, 3 patients with delayed HS confirmed by a ST (11.1%) were misclassified. The AUC was significantly higher for PEN-FAST+ than PEN-FAST (85% vs. 72%, p=0.03).